DEVELOPMENT OF A GUIDED INQUIRY-BASED CHEMISTRY MODULE ON PERIODIC SYSTEM OF ELEMENTS MATERIAL - Siregar, Tiurlina; Marthen Inggamer, Mamberuman; Samosir, Rendra Christian (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2024)
The availability of modules as teaching materials is very limited so it is an obstacle in learning chemistry, especially material on the periodic system of elements. Therefore, this research aims to develop and validate the feasibility of a chemistry module on material on the periodic system of elements based on guided inquiry and to analyze how students and teachers respond to the product being developed. The research and development (R&D) method is the method used and ADDIE is the development model applied as a methodology. The module developed is very suitable for application in chemistry learning, according to the results of the analyzed data. The average assessment from validators is 95% very decent and the response from colleagues is 98% very good, the student response is 97% very good